Effects of cooking beef muscles from frozen or thawed states on cooking traits and palatability - E. Obuz; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2002)
We used an electric belt grill to cook steaks from two muscles; outside round (biceps femoris), and loin strip (longissimus lumborum) from both frozen and thawed states. The color values L* and a*, Warner-Bratzler shear force (WBSF), juiciness, flavor, connective tissue amount, and overall tenderness did not differ (P>0.05) between steaks cooked from frozen and thawed states. Thawed steaks cooked faster and had less cooking loss. The biceps femoris had higher WBSF than longissimus and was rated less tender by trained panelists. Color values L*, a*, or b* did not differ (P>0.05) among the muscles. The biceps femoris needed more time to cook and had greater cooking loss than longissimus.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Cooking; Belt grill; Frozen or thawed steaks